Industrial characteristics of Spanish native almond cultivars and their interest for breeding programs - Romero A.; Miarnau X.; Dicenta F.; Batlle I. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The displacement of almond orchards towards inland regions of Spain with high risk of spring frost fostered the use of self-compatible late-flowering varieties, adapted to these new areas. This fact is causing a progressive reduction of Spanish native, early flowering and self-incompatible local cultivars, many of them at risk of extinction or already extinct. Native varieties were selected over the years for their adaptation to the warm Mediterranean climate conditions and their high organoleptic quality. In addition, traditional confectionery products are based on particular characteristics of these cultivars. The first results on the industrial aptitude of these native cultivars are reported. It is outstanding the absence of cultivars with a high toasting aptitude and those with a broad shape.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)